Analisis Terhadap Input Proses Output Pelaporan Pada Sistem Informasi Manajemen Puskesmas (SIMPUS) - Pragandari Rosaliana, Septi; Lestari, Tri; Bayu Sinta, Tunjung (Indonesian Journal of Health Information Management, 2026)
Reporting is the delivery of disaggregated data from recording results to related parties in accordance with predetermined goals and needs. The aim of this research is to determine the implementation of reporting on the Community Health Center Management Information System (SIMPUS) at Masaran II Sragen Community Health Center based on input, process and output elements. This research uses descriptive research with a cross sectional approach. The subjects of this research were 2 SIMPUS users, consisting of 1 medical records officer in the registration section as the data input officer and 1 SIK coordinator officer as the reporting officer in the data process and output section. The object of this research is the implementation of SIMPUS reporting. The instruments used are observation guidelines and interview guidelines. Data collection method is by observation and structured interviews. Data processing techniques using data collection, data editing and data presentation. The data analysis used is the descriptive analysis method. The research results show that the SOP / reporting policy at SIMPUS has not been created / formulated. The source of data input comes from the patient's identity card, reports are prepared by each health unit and reports produced from e-Puskesmas include daily, weekly, monthly and annual reports while the reports sent to the DKK are reports on the number of patient visits, UKP, UKM, UKME, UKMP, but there are still obstacles in working on the report, namely an unstable internet network connection. It would be best to increase the bandwidth of the internet network in collaboration with the provider from 50 mbps to 100 mbps so that there are no more internet disruptions, so that there are no problems in service process either in the registration section or processing in the reporting section.